The great equalizer: Effects of Chinese official finance on economic complexity across recipient countries - Jan Denninger; Lennart Kaplan (Kiel Institute for the World Economy (IfW Kiel), 2025)
This paper analyzes whether Chinese aid and other forms of official finance affect structural transformation in low- and-middle income countries. Specifically, we employ an instrumental variables (IV) approach to causally analyze the effect on the Economic Complexity Index of 98 recipient countries over the 2002-2016 period. Economic complexity is defined as the diversity and sophistication of the goods an economy produces. The results reveal that Chinese official financing (OF) does not have statistically significant effects at the aggregate level; however, its effectiveness varies across sectors and recipients. A sectoral perspective shows that Chinese OF to recipients' production sectors has a significantly negative effect on their economic complexity. These effects are most pronounced for high-complexity recipients, suggesting that China primarily targets industries below existing levels of complexity, thereby impeding potential structural transformation. In contrast, low-complexity recipients experience positive complexity effects from Chinese social sector projects, especially from those related to education. Given that China is known for its demand-driven approach of lending, recipients should push for an adjustment in the composition and allocation of Chinese OF to render structural transformation more likely.
Keywords: P45; F14; F35; O11; O35; 330; Aid; China; Trade; Economic Complexity; Structural Change